Data (Video) Encryption in Mobile Devices - Naji, Aya Khalid; Alsaad, Saad Najim (Kurdistan Journal of Applied Research, 2017)
In the development of 3G devices, all elements of multimedia (text, image, audio, and video) are becoming crucial choice for communication. The secured system in 3G devices has become an issue of importance, on which lot of research is going on. The traditional cryptosystem like DES, AES, and RSA do not able to meet with the properties of the new generation of digital mobile devices. This paper presents an implementation of video protection of fully encrypted using Elliptic Curve Cryptography (ECC) on a mobile device. The Android platform is used for this purpose. The results refer that the two important criteria of video mobile encryption: the short computation time required and high confidentially are provided.